Evaluasi dan Audit Mutu Pendidikan dalam Perspektif Manajemen Mutu Terpadu - Nur Malik, Novi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The evaluation and quality audit of education are essential components of the Total Quality Management (TQM) system in educational institutions. In the context of Islamic education, the implementation of evaluation and quality audits not only targets administrative and academic aspects but also encompasses spiritual and moral values. This article aims to analyze the process of educational evaluation and quality audits, as well as their implementation in supporting the quality improvement of Islamic educational institutions. This research employs a descriptive qualitative approach using a literature review method. The findings indicate that systematic evaluations and periodic internal and external audits can foster the development of a sustainable quality culture. These findings contribute to the overall improvement of the quality management system in Islamic educational institutions.